ЕКСПЕРИМЕНТАЛЬНЕ ВИЗНАЧЕННЯ ВЕЛИЧИНИ СТРУМУ ВИТОКУ ІЗОЛЯТОРІВ МАРКИ ШФ-20 У РІЗНИХ ТЕХНІЧНИХ СТАНАХ - Буйний, Р.О.; Строгій, А.Ю. (Інститут електродинаміки Національної академії наук України, 2025)
The paper presents the results of an experimental study on the effect of damage to pin-type insulators of the ShF-20 type under different degrees of moisture on the leakage currents and the capacitance of the "conductor-insulator-pin" system. Leakage currents through the insulators were experimentally measured under direct and alternating current, as well as in dry, moderately moist, and wet conditions. Based on these currents, the capacitance of the "pin-insulator-conductor" system was calculated and compared with the results of computer modeling. It was found that the calculated capacitance values consistent with the computer modeling results. It was also established that mechanical defects in the insulators do not affect their capacitance value; however, the active component of the leakage current can be used as a diagnostic indicator of the degree of insulator contamination in its dry state and as an indicator of the initial stage of its degradation. Ref. 9, fig. 7, tables 9.